Taxonomic and nomenclatural notes on African Linum squarrosum sensu lato (Linaceae) - Martínez Labarga, Juan M.; Ferrer-Gallego, P. Pablo (Phytotaxa, 2020)
The taxonomy and nomenclature of Linum squarrosum s.l. (Linaceae) is discussed. Two subspecies are identified in this species. A new combination and status is proposed, L. squarrosum subsp. maroccanum comb. & stat. nov. Original material preserved at K is designated as the lectotype of Linum squarrosum, and a specimen kept at BC is selected as the lectotype of L. squarrosum subsp. maroccanum (=L. suffruticosum var. maroccanum).